Astragalus membranaceus nanoparticles markedly improve immune and anti-oxidative responses; and protection against Aeromonas veronii in Nile tilapia Oreochromis niloticus. Issue 97 (February 2020) - Elabd, Hiam; Wang, Han-Ping; Shaheen, Adel; Matter, Aya
Abstract: The effects of dietary administration of Astragalus membranaceus nanoparticles (ANP) on immune and anti-oxidative responses, growth performance and disease resistance of Oreochromis niloticus were evaluated in the present study. Fish were divided into three groups and received the ANP at rates of 0 (control), 1, and 2%/kg diet for four weeks. After the four-week feeding trial, three fish from each replicate were sampled for immune and anti-oxidative responses evaluation, ten fish from each group were challenged with A. veronii, and nine fish from each group were subjected to cold and hypoxia challenges. It was obvious from the results that ANP significantly enhanced lysozyme activity and nitrous oxide (NO) activities, as well as improved superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities. Also, aspartate aminotransferase, alanine transaminase, glucose, and cortisol measurements showed significantly lower levels in incorporated groups compared to the control. Growth performance; and amylase and lipase digestive enzymes activities also showed markedly improved results. Expression of heat shock protein 70 (HSP70) and interleukin 1, beta (IL-1β) genes were significantly upregulated throughout the entire experimental period. When challenged with A. veronii, the mortality of treated groups was significantly (P < 0.05) lower than the control. Current results proofs that dietary ANP had a synergistic effect on immune and anti-oxidative responses, growth performance and disease resistance of Oreochromis niloticus . Highlights: ANP markedly enhanced disease and stress resistance of Oreochromis niloticus. ANP improved immune and anti-oxidative responses. ANP markedly up-regulated related genes expression. Supplemented groups revealed better growth performance and digestive enzymes activity. ANP has the ability to confer protection against different physical stressors.